Assessment of corporate social responsibility and its impacts on corporate reputation of companies in selected Balkan Countries former Yugoslavia States - Lu, Jintao; Ren, Licheng; Zhang, Chong; Qiao, Jiayuan; Kovacova, Maria; Streimikis, Justas (Technological and Economic Development of Economy, 2020)
The empirical study was conducted in the three selected Balkan Countries from former Yugoslavia: Slovenia, Croatia and Montenegro through totally 270 experts’ surveys, 90 questionnaires were distributed to entrepreneurs (30), policy makers (30) and experts from academia (30) in each country in order to assess the CSR level in the country and the effect the main drivers having on CSR level, then followed by the assessment of CSR impacts on Corporate Reputation (CR). The model of multivariate regression was developed for assessment of the impact of the four independent variables (Institutional Environment, Executive Characteristics, Customers’ Expectations and Political Factors) on dependent variable–CSR. The study also analysed the impact of CSR (dependent variable) on CR. The obtained results show that countries with the higher level of CSR, have achieved the greater level of CR. The degree of the impact of the main drivers on CSR in selected Balkan countries is linked to EU accession level. The political factor has the highest impact on CSR level in all investigated countries, institutional environment is the next.